Navigating the Diagnostic Maze: A Case Report of Uncommon Cardiac Metastasis in Childhood Ewing Sarcoma - Balaji Narayanan; Jitendra Sharma; Meenakshi Ahuja; Raghavendra Kamalesh; Ujjawal Khurana; Rajesh Malik (Indian Journal of Medical and Paediatric Oncology)
Ewing sarcoma is a bone cancer affecting children and young adult males. It usually presents as a single bone tumor, but it can also occur in multiple locations. Nevertheless, Ewing sarcoma is an extremely aggressive tumor capable of metastasizing to other parts of the body, such as the lungs, bones, liver, and lymph nodes. Cardiac metastases are rare, indicating a poor prognosis, as they suggest that the cancer has become more advanced and challenging to treat.